EUPRON: nurses' practice in interprofessional pharmaceutical care in Europe. A cross-sectional survey in 17 countries. Issue 6 (3rd June 2020) - De Baetselier, Elyne; Van Rompaey, Bart; Batalha, Luis M; Bergqvist, Monica; Czarkowska-Paczek, Bozena; De Santis, Alberto; Dijkstra, Nienke E; Fernandes, Maria I; Filov, Izabela; Grøndahl, Vigdis Abrahamsen; Heczkova, Jana; Helgesen, Ann Karin; et al.
Abstract : Objectives: Safe pharmaceutical care (PC) requires an interprofessional team approach, involving physicians, nurses and pharmacists. Nurses' roles however, are not always explicit and clear, complicating interprofessional collaboration. The aim of this study is to describe nurses' practice and interprofessional collaboration in PC, from the viewpoint of nurses, physicians and pharmacists. Design: A cross-sectional survey. Setting: The study was conducted in 17 European countries, each with their own health systems. Participants: Pharmacists, physicians and nurses with an active role in PC were surveyed. Main outcome measures: Nurses' involvement in PC, experiences of interprofessional collaboration and communication and views on nurses' competences. Results: A total of 4888 nurses, 974 physicians and 857 pharmacists from 17 European countries responded. Providing patient education and information (PEI), monitoring medicines adherence (MMA), monitoring adverse/therapeutic effects (ME) and prescribing medicines were considered integral to nursing practice by 78%, 73%, 69% and 15% of nurses, respectively. Most respondents were convinced that quality of PC would be improved by increasing nurses' involvement in ME (95%), MMA (95%), PEI (91%) and prescribing (53%). Mean scores for the reported quality of collaboration between nurses and physicians, collaboration between nurses and pharmacists and interprofessional communication were respectively <7/10, ≤4/10, <6/10 for all four aspects of PC. Conclusions: ME, MMA, PEI and prescribing are part of nurses' activities, and most healthcare professionals felt their involvement should be extended. Collaboration between nurses and physicians on PC is limited and between nurses and pharmacists even more.